PERAN SANGGAR PENGAWAS DAN PENGAWAS SEKOLAH DALAM PENJAMINAN MUTU PENDIDIKAN DI SEKOLAH: Suatu Studi Deskriptif Kualitatif pada Pengawas SMP di Lingkungan Dinas Pendidikan Kabupaten Lumajang, Jawa Timur - Jaryono, - (2011)
This research based on the importance of school supervisor's role and function, particularly on secondary junior high school, for education quality assurance in school base. Considering the importance role of school supervisors, educational authority provide a sort of community of practice to improve quality and competence of school supervisors. This research attempt to figure out how community of practice for school supervisors play role in developing and increasing skill and supervisor's competence.This research also try to reveal the role and performance of school supervisor in school quality assurance process. This research use descriptive qualitatif model which has characteristic in data in narative form. In this research, collecting data is conducted by indepth interview and observation and also document studies. Indepth interview and observation and document studies lead by interview and observation guidance. Data analysis will be perform by data reduction, making data model and data display for conclusion drawing. The result of data analysis can be concluded that supervisor forum has not sufficient role in developing and increasing skill and supervisor's competence. Supervisors forum are not play a role as community of practice. Supervisor forum also does not has a program to increase and to develop supervisor's skill and competence. School supervisors also have less role in quality assurance process because school outnumber and insufficient knowledge and skill about quality assurance at the school. Keyword : supervisor forum, school supervisor, education quality assurance, school quality